Preparing a change laboratory intervention: waste management in a University hospital - Cassandre, Marcio Pascoal; Senger, Carine Maria; Querol, Marco Antonio Pereira (RACE - Revista de Administração, Contabilidade e Economia, 2018)
Abstract: Researchers, interventionists and managers are challenged to plan an intervention for the development of an activity. To this purpose, it is necessary to understand and negotiate the object of the intervention with the participants. This task can be facilitated through the elaboration of a research scheme used as a planning and learning tool among interventionists and participants. This article presented an outline of such scheme for future application of a Change Laboratory (CL). This lab is considered a method to provide the development of the solid waste management activity in a university hospital in Paraná State, Brazil. The study shows the aspects to be explored to plan a CL in order to develop a new concept of this activity. It is a draft for the planning of these methodology sessions. Its preparation makes use of preliminary ethnographic data collected during the beginning of the investigative procedure foreseen by CL, seeking the current conflict historical understanding. Keywords: Activity Theory. Change Laboratory. Waste Management. University Hospital. Preparando uma intervenção do Laboratório de Mudança: a gestão dos resíduos de um hospital universitário Resumo: Pesquisadores, intervencionistas e gestores são desafiados a planejar uma intervenção visando ao desenvolvimento de uma atividade. Para tanto, faz-se necessário entender e negociar o objeto da intervenção com os participantes. Tal tarefa pode ser facilitada por meio da elaboração de um esquema usado como instrumento de planejamento e aprendizagem entre intervencionista e participantes. Neste artigo apresentou-se um esboço deste esquema para a aplicação futura de um Laboratório de Mudança (LM). Este laboratório é considerado um método para propiciar o desenvolvimento da atividade de gestão de resíduos sólidos em um hospital universitário do Paraná. O estudo mostra os aspectos a serem explorados para planejar um LM visando desenvolver um novo conceito dessa atividade. Trata-se de um rascunho para o planejamento das sessões dessa metodologia. Sua elaboração faz uso de dados etnográficos preliminares coletados durante o início do processo investigativo previsto pelo LM, buscando a compreensão histórica da atual situação do conflito. Palavras-chave: Teoria da Atividade. Laboratório de Mudança. Gestão de Resíduos. Hospital Universitário.